Construction of an Index to Assess the Awareness of Horticultural Farmers towards e-Extension Services - Vishal Sahu; V K Singh; Saikat Maji; Raj Lakshmi; Monu Kumar; Mohit Singh (Indian Journal of Extension Education, 2026)
The rapid expansion of Information and Communication Technologies (ICTs) has reshaped agricultural extension, offering scalable pathways for disseminating timely, location-specific information to farmers. Horticulture crops are highly perishable in nature and decision-making time-sensitive; the effectiveness of e-extension systems depends strongly on farmers’ awareness and understanding of digital advisories. This present study, conducted during 2025, aimed to construct a scientifically valid and reliable index to measure the awareness of horticultural farmers towards e-extension services. Based on an extensive literature review, expert consultations, and field insights, 112 statements were initially generated across three conceptual domains: general awareness about e-extension, awareness of public e-extension services, and awareness of private e-extension services. Following rigorous screening using Edward’s criteria and relevancy testing by 70 experts, 48 statements met the established criteria of Relevancy Weightage (≥0.80) and Mean Relevancy Score (≥OMRS = 2.44). The index was validated through field administration among 60 horticultural farmers in non-sampled areas. Reliability analysis indicated excellent internal consistency (Cronbach’s alpha = 0.951) and strong split-half reliability (Spearman-Brown coefficient = 0.936). The validated index provides a robust measurement framework to assess awareness gaps and strengthen ICT-enabled advisory systems, thereby enhancing the accessibility, effectiveness, and impact of e-extension services in the horticultural sector.